Analysing the scientific literature on transgender and gender diverse persons’ experiences with sexual and reproductive health care services from an intersectional perspective - Susan Heward-Belle; Sarah Ciftci; Renee Lovell (International Journal for Equity in Health)
Abstract Transgender and gender diverse (TGD) persons face considerable challenges accessing sexual and reproductive health care (SRHC), often resulting in poor health outcomes when compared to cisgender persons. Aetiological research predominantly explains these health disparities through a single axis explanation reducing them to factors related to gender identity. Yet, a one-dimensional representation of TGD persons fails to recognize the multiple experiences of systemic oppression that may contribute to poor sexual and reproductive health (SRH) experiences and outcomes. This scoping review was conducted to locate, analyse and synthesise contemporary scientific research exploring TGD persons’ experiences with SRHC services, from an intersectional perspective. Searches were conducted in PsycINFO, APA Psychinfo, Ovid MEDLINE®, SCOPUS, and CINAHL. Studies were included if they were in English, conducted in OECD countries, published between 2012 to 2022 in peer-reviewed journals, based upon empirical research, involving human participants and presenting disaggregated data for TGD populations. To be included, studies also had to contain TGD individuals who had accessed SRHC services and data that pertained to forms of oppression, disadvantage, social determinants of health or aspects of identity that intersected with their gender identities. 1290 records were identified and entered into Endnote software X9, with 413 removed before screening. A total of 877 records were screened by the author and a research assistant independently who examined titles and abstracts and selected 27 for in-depth analysis. Included studies were uploaded to NVivo 12 and subjected to in-depth review, coding, and synthesis using descriptive statistics and thematic analysis. The review found that efforts to understand TGD persons’ experiences of multiple marginalisation in SRHC settings are hampered by methodological challenges relating to adopted sampling techniques, measures used, the use of small and non-representative samples, and geographic location. The review found multiple intersecting systems of oppression including cissexism, heterosexism, racism, classism, geographical disadvantage and ageism, that challenged TGD persons’ access to quality care within SRHC settings. Best practices were identified including affirming, person-centred care, collaboration, trauma-informed care and leveraging informal support networks, which provide hope for improved service provision and design.